2010
DOI: 10.1007/s10811-010-9582-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen peroxide on the content of major volatile halogenated compounds in the red alga Asparagopsis taxiformis (Bonnemaisoniaceae)

Abstract: The genus Asparagopsis is a prolific source of halogenated metabolites. Due to its commercial applications, it has been intensively cultivated in southern Portugal. In the present study, we assess if the internal levels of the major halogenated metabolites (bromoform and dibromoacetic acid) in Asparagopsis taxiformis can be increased with hydrogen peroxide (H 2 O 2 ) addition. Previous studies with red algae showed that the production/release of bromoform can be enhanced by exogenously supplying H 2 O 2 . Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…A (indicative of sp 3 C) and a Br shell at 3.15-3.20 A (i.e., one or more "geminal" bromine scatterers, attached to the same carbon as the absorber). This is in line with the observation that this alga is by orders of magnitude more active in evolving bromoform and analogs than the others (Carpenter et al 2000, Mata et al 2011). Asparagopsis species contain many different geminal dibromo and tribromo compounds (e.g., Woolard et al 1976).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A (indicative of sp 3 C) and a Br shell at 3.15-3.20 A (i.e., one or more "geminal" bromine scatterers, attached to the same carbon as the absorber). This is in line with the observation that this alga is by orders of magnitude more active in evolving bromoform and analogs than the others (Carpenter et al 2000, Mata et al 2011). Asparagopsis species contain many different geminal dibromo and tribromo compounds (e.g., Woolard et al 1976).…”
Section: Resultssupporting
confidence: 90%
“…, Mata et al. ). Asparagopsis species contain many different geminal dibromo and tribromo compounds (e.g., Woolard et al.…”
Section: Resultsmentioning
confidence: 99%
“…2001). However, Mata et al. (2011) showed that this was not the case of bromoform content of A. taxiformis under long‐term exposure to H 2 O 2 enrichment.…”
Section: Discussionmentioning
confidence: 91%
“…The production of halogenated metabolites by seaweeds may be promoted by substrates and cofactors (e.g., bromide ions or hydrogen peroxide) involved in the activity of haloperoxidase, the enzyme responsible for the biogenesis of halogenated metabolites (Sundström et al 1996, Ohsawa et al 2001). However, Mata et al (2011) showed that this was not the case of bromoform content of A. taxiformis under long-term exposure to H 2 O 2 enrichment.…”
mentioning
confidence: 89%
“…Consequently volatile halogenated compounds will be formed as shown by several authors. [66][67][68][69][70][71][72] It is well known that plant cells during photosynthesis and photorespiration generate H 2 O 2 . 73 Also intra-and intercellular levels of H 2 O 2 increase during environmental stresses experienced by plant cells.…”
Section: Effect Of Light H 2 O 2 and Stress On Bromoform Production mentioning
confidence: 99%